Determination of the macroscopic optical properties of snow based on exact morphology and direct pore-level heat transfer modeling - Haussener, Sophia; Gergely, Mathias (Journal of geophysical research. Earth surface, 2012)
A multiscale methodology for the determination of the macroscopic optical properties of snow is presented. It consists of solving the coupled volume-averaged radiative transfer equations for two semi-transparent phases - ice and air - by Monte Carlo ray tracing in an infinite slab via direct pore-level simulations on the exact 3D microstructure obtained by computed tomography. The overall reflectance and transmittance are computed for slabs of five characteristic snow types subjected to collimated and diffuse incident radiative flux for wavelengths 0.3-3 μm. The effect of simplifying the snow microstructure and/or the radiative transfer model is elucidated by comparing our results to (i) a homogenized radiation model and considering a particulate medium made of optical equivalent grain size spheres (DISORT), or (ii) a multiphase radiation model considering a packed bed of identical overlapping semi-transparent spheres. The calculations are experimentally validated by transmittance measurements. Significant differences in the macroscopic optical properties are observed when simplifying the snow morphology and the heat transfer model (i.e., homogenized versus multiphase). The proposed approach allows - in addition to determine macroscopic optical properties based on the exact morphology and obtained by advanced heat transfer model - for detailed understanding of radiative heat transfer in snow layers at the pore-scale level.